Household water sharing: a missing link in international health. Issue 3 (20th December 2018) - Stoler, Justin; Brewis, Alexandra; Harris, Leila M; Wutich, Amber; Pearson, Amber L; Rosinger, Asher Y; Schuster, Roseanne C; Young, Sera L
Abstract: Water insecurity massively undermines health, especially among impoverished and marginalized communities. Emerging evidence shows that household-to-household water sharing is a widespread coping strategy in vulnerable communities. Sharing can buffer households from the deleterious health effects that typically accompany seasonal shortages, interruptions of water services and natural disasters. Conversely, sharing may also increase exposure to pathogens and become burdensome and distressing in times of heightened need. These water sharing systems have been almost invisible within global health research but need to be explored, because they can both support and undermine global public health interventions, planning and policy.